The Effectiveness of Mathematics Instruction through the Implementation of the Jigsaw Cooperative Learning Model on the Topic of Quadratic Equations - Siregar, Torang (Annals of Mathematics and Physics, 2026)
This study employed a quasi-experimental design involving two groups—an experimental group and a control group—with the objectives of (1) examining the mathematics learning outcomes of Grade X-A students at SMA Negeri 2 Padangsidimpuan, North Sumatra, Indonesia, taught using the Jigsaw cooperative learning model; (2) assessing the mathematics learning outcomes of Grade X-B students at the same school taught using conventional instruction; and (3) determining whether the Jigsaw cooperative learning model yields significantly better mathematics learning outcomes than conventional instruction in the topic of quadratic equations. The sample comprised the entire population of 60 students, with 30 assigned to the experimental group and 30 to the control group. Data were collected using standardized instruments administered during the first and final class meetings. Descriptive and inferential statistical analyses were conducted. Descriptive results indicated that students taught with the Jigsaw model achieved a “very high” performance level (43.33% of students, mean score = 73.50% of the ideal maximum of 100, SD = 20.892), whereas those taught conventionally scored in the “very low” category (33.33% of students, mean score = 43.50, SD = 20.726). Inferential analysis confirmed that the Jigsaw cooperative learning model significantly enhanced student achievement in quadratic equations compared to conventional teaching methods. Therefore, the implementation of the Jigsaw model effectively improves mathematics learning outcomes among Grade X students at SMA Negeri 2 Padangsidimpuan.